The Phantom Opportunity: Bridging the Gap Between Idea and Equity Investors - Caston, Michael; Purtell, Clint; Grumbles, Lee; Flink, Nicole (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
Kirznerian entrepreneurs are described as alert individuals apt to identify opportunities through subjective inferences based on industry competition, price inequality, and interaction with other market actors. They are poised to identify and exploit opportunities that may not currently exist. We extend this notion of alertness towards the unknown by introducing the “phantom opportunity” concept, extending prior research. Although entrepreneurs may initially perceive a new venture idea, it cannot manifest itself as opportunity until other parties legitimize it by mutually perceiving it as such, thus committing resources. For example, investors may mentally simulate, contributively co-create or modify a proposed opportunity before committing the necessary funding to launch the entrepreneur’s perceived idea. This paper extends Kirzner’s view of perception and opportunity as related to the modern entrepreneurs’ struggle to define, legitimize and realize an opportunity.